Studi Eksperimen Pengaruh Ukuran Bahan Bakar Terhadap Kerja Pada Reaktor Fluidized Bed Gasifier - Descesar P.W, Ary, Nur Aklis,ST,M.Eng (2017)
Abstract The aims of the research is to determine the effect of fuel particle size on the performance of fluidized bed reactor. The research was performed on reactor with a diameter of 454.38 mm and 908.5 mm combustion chamber high. The fuel used rice husk with the variation of size 1.54mm, 1.84 mm, 2.17 mm and particles bed is silica sand used with the size of 0.54 mm. The data are taken contained of the minimum speed fluidization, the temperature of the reactor, time of reaction, length of time to boil the water by as much as 2 liters. The combustion process for a one time use 5 kg of rice husk, 10 kg of silica sands, and chalk 1 kg. The results showed that the size of the fuel affects the minimum speed fluidization. Average temperature highes of reactor is 237 (°C) during the examination with rice husk using a variation of size 1.84 mm.Fastest time of reaction is 55 minute conducted on the examination by using a variation of rice husk size 1.54 mm. Fastest time to boil water as much as 2 liters is 40 minutes on an examination by using rice husk size 2.17 mm. Greatest amount of heat is generated that is 1870.083 kJ conducted on the examination using rice husk size 1.54 mm. Keywords: Rice Husk, Fluidized Bed Gasifier, The Size Of The Fuel